Analisis Hukum Pencegahan dan Pemberantasan Perusakan Hutan Kaitannya dengan Potensi Kekosongan Hukum dalam Perspektif Penyidikan Tindak Pidana Kehutanan - Turnip, Palber; Suhaidi, Suhaidi; Harianto, Dedi; Rafiqi, Rafiqi (ARBITER: Jurnal Ilmiah Magister Hukum, 2020)
The issuance of Law No. 18 Year 2013 concerning the Prevention and Combating DeforestationÂ  promulgatedÂ  date of August 6, 2013, has declared unplug and do not apply some rules of the offense in Law No. 41 of 1999 on Forestry allegedly can lead to potential Emptiness Law, which can lead to increased threats to forest destruction. Therefore, efforts to fill the legal vacuum intended to reduce the potential destruction of forests. This research is normative juridical typology synchronization research laws and regulations. While the nature of the research is descriptive analitif. From the data collected, analyzed, and then can be concluded that the issuance of Law No. 18 Year 2013 has changed the rules that have been good in Law No. 41 of 1999 which would cause a vacuum in the law with the absence of binding rules to a acts that could destroy the forest.